Supersonic propagation of ionization waves in an underdense, laser-produced plasma - Constantin, C; Back, C; Fournier, K; Gregori, G; Landen, O; Glenzer, S; Dewald, E; Miller, M (2005)
A laser-driven supersonic ionization wave propagating through a millimeter-scale plasma of subcritical density up to 2-3 keV electron temperatures was observed. Propagation velocities initially ten times the sound speed were measured by means of time-resolved x-ray imaging diagnostics. The measured ionization wave trajectory is modeled analytically and by a two-dimensional radiation-hydrodynamics code. The comparison to the modeling suggests that nonlocal heat transport effects may contribute to the attenuation of the heat-wave propagation. © 2005 American Institute of Physics.